An experimental xenograft mouse model of diffuse pontine glioma designed for therapeutic testing - Aoki, Yasuyuki (2012)
The prognosis for diffuse infiltrating pontine gliomas (DIPG) remains extremely poor, with the majority of patients surviving less than 2 years. Here, we have adapted standard xenograft techniques to study glioma growth in the mouse brainstem, and have utilized the mouse model for studying a relevant therapeutic for treating DIPGs. bioluminescence imaging monitoring revealed a progressive increase in signal following the injection of either of two tumor cell types into the brainstem. Mice with orthotopic GS2 tumors, and receiving a single 100 mg/kg dose of temozolomide showed a lengthy period of decreased tumor luminescence, with substantially increased survival relative to untreated mice (P<0.001). A small molecule inhibitor that targets cdk4/6 was used to test AM-38 brainstem xenograft response to treatment. Drug treatment resulted in delayed tumor growth, and significantly extended survival. Our results demonstrate the feasibility of using an orthotopic brainstem tumor model in athymic mice, and for application to testing therapeutic agents in treating DIPG.